Penggunaan Metode Full Costing Dan Variable Costing Terhadap Laba Bersih UMKM “Noen Cookies” : The Use of Full Costing and Variable Costing Methods on the Net Profit of the “Noen Cookies” SME - Nazwa Safira Maharani; Lina Rosalina; Nabila Azzahra; Alifasha Muthia; Tri Lestari (CV Warnak Johanna Nusantara, 2025)
This analysis applies a descriptive qualitative approach based on how to obtain data using comprehensive interviews with business owners, as well as record keeping related to raw material costs and overhead costs. The Full Costing calculation includes a total of all raw material costs of Rp 928,400 and overhead costs of Rp 727,622, resulting in a Cost of Goods Sold (COGS) per unit of Rp 18,000.24 and a net profit of Rp 2,010,978. Meanwhile, the Variable Costing approach simply considers raw material costs as variable costs, resulting in a Cost of Goods Sold per unit of Rp 10,091.30 and a net profit of Rp 2,738,600. The analysis that has been conducted reveals that the Variable Costing approach produces a higher profit signal because it does not consider overhead costs in the cost of goods manufactured. Therefore, the Variable Costing approach is assumed to be more accurate to be applied to MSMEs such as Noen Cookies that implement a pre-order system, experience fluctuations in production volume, and have relatively simple financial records.